Feasibility and early toxicity of focal or partial brachytherapy in prostate cancer patients - Kim, Tae Heon (J Contemp Brachytherapy, 2020)
PURPOSE: The aim of this study was to compare short-term oncologic outcomes and toxicity of focal or partial low-dose-rate brachytherapy (focal/partial LDR-BT) with whole gland low-dose-rate brachytherapy (whole LDR-BT) in localized prostate cancer patients. MATERIAL AND METHODS: Medical records of eligible patients who underwent focal/partial LDR-BT and whole LDR-BT between 2015 and 2017 at our institution were reviewed retrospectively. Clinical characteristics and pathologic outcomes were compared between focal/partial LDR-BT group and whole LDR-BT group. Biochemical recurrence-free survival was analyzed using Kaplan-Meier method and difference between two groups was assessed with log-rank test. Genitourinary and rectal toxicity were also evaluated between the two groups. RESULTS: Of the 60 patients analyzed, 30 focal/partial LDR-BT patients and 30 whole LDR-BT brachytherapy patients were included. Relative to the whole LDR-BT group, the focal/partial LDR-BT group had significantly higher initial PSA level (p = 0.002), smaller number of implanted seeds (p < 0.001), and shorter follow-up duration (p < 0.001). There was no significant difference between the two groups with regard to prostate volume, biopsy Gleason score, and risk group stratification. The 3-year biochemical recurrence-free survival estimates for focal/partial LDR-BT group and whole LDR-BT group were 91.8% and 89.6%, respectively, which was not significantly different (p = 0.554). Genitourinary symptoms were significantly worse in whole LDR-BT group than in focal/partial LDR-BT group. The incidence of rectal toxicity was similar between two groups. CONCLUSIONS: Our findings indicate that the focal/partial LDR-BT is comparable to the whole LDR-BT with respect to short-term biochemical recurrence and toxicities.